Polymer-based fluid loss reducer for oil well cement and preparation method thereof

By adopting a water loss reduction agent for multipolymer oil well cement, combined with the specific composition and synthesis process of polymer polymers and composite hydrating agents, the existing water loss reduction agents have been solved, and a more efficient cementing effect of cement slurry is achieved.

CN119285267BActive Publication Date: 2025-03-14PANJIN HONGBO PETROLEUM TECH SERVICE CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411823472.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-03-14
Estimated Expiration
2044-12-12

AI Technical Summary

Technical Problem

The existing water loss reduction agents have poor water loss and temperature and salt resistance, which cannot effectively solve the problem of filtration loss of oil well cement slurry in high temperature and high pressure environments.

Method used

The water loss reduction agent for multipolymer oil well cement is used, consisting of polymer polymers, bentonite, disodium ethylenediaminetetraacetate, composite hydrating agent and distilled water. Through specific synthesis steps and process conditions, its water loss reduction and temperature and salt resistance are improved.

Benefits of technology

It significantly improves the water loss and temperature and salt resistance of the water loss agent, and enhances the fluidity and early strength of the cement slurry, and improves the quality and safety of cementing operations.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses a multipolymer oil well cement fluid loss reducer and a preparation method, and belongs to the technical field of fluid loss reducer preparation. The multipolymer oil well cement fluid loss reducer is composed of the following components in parts by weight: 42-56 parts of high molecular weight polymer, 4-6 parts of bentonite, 1-3 parts of disodium ethylenediaminetetraacetate, 10-13 parts of composite hydrating agent, 8-12 parts of distilled water, and 0.2-0.4 parts of ammonium persulfate, wherein the high molecular weight polymer is prepared from dimethylaminopropyl acrylamide, 2-acrylamide-2-methylpropanesulfonic acid, glycidyl methacrylate, 3-propane-2-acryloxypropane-1-sodium sulfonate and 2-aminoethanethiol, and the composite hydrating agent is prepared from acrylic acid, 2-acrylamide-2-methylpropanesulfonic acid, sodium lignin sulfonate, corn fiber and butyl succinic anhydride. The fluid loss reducer prepared by the method has excellent fluid loss reduction performance and temperature and salt resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of fluid loss reducer preparation, and in particular relates to a multi-polymer fluid loss reducer for oil well cement and a preparation method thereof. Background Art

[0002] In the process of oil exploration and development, cementing operations are one of the key links to ensure the stability of oil wells and improve oil recovery. As the main material for cementing operations, the performance of cement slurry directly affects the quality of cementing and the long-term safety of oil wells. However, in the complex geological conditions and high temperature and high pressure downhole environment, cement slurry faces serious filtration problems, that is, the water in the cement slurry is easily lost through the formation pores, resulting in the degradation of cement slurry performance and the damage of cementing quality. In oil well cement slurry, multi-polymer water-loss reducers form a dense protective film through adsorption, bridging and cross-linking mechanisms, effectively preventing the water in the cement slurry from penetrating into the formation. At the same time, water-loss reducers can also improve the fluidity of cement slurry, reduce its viscosity, and make it easier to pump and construct in the downhole environment. In addition, they can also improve the early strength and impermeability of cement slurry, ensuring the quality and safety of cementing operations.

[0003] Patent CN 114395074 B discloses an organic-inorganic hybrid fluid-loss agent for oil well cement, and its preparation method and application. The preparation method is as follows: add 2-acrylamide-2-methylpropanesulfonic acid, acrylamide monomers, carboxylic acid monomers and sodium p-styrene sulfonate to distilled water, stir evenly at room temperature, and adjust the pH; after adding an initiator, heat the reaction to obtain a liquid anionic polymer fluid-loss agent; mix the liquid anionic polymer fluid-loss agent with magnesium-aluminum hydrotalcite, stir for 6-8h at 65-75°C, settle, wash, centrifuge, freeze-dry and grind to obtain an organic-inorganic hybrid fluid-loss agent for oil well cement. The invention uses water as a dispersion medium, has a simple preparation process, can effectively reduce the water loss of cement slurry at high temperature, and improves the over-slow setting phenomenon caused by a single polymer fluid-loss agent to cement slurry, but the fluid-loss reduction and temperature and salt resistance of the fluid-loss agent prepared by this method still have room for improvement. Summary of the invention

[0004] The object of the present invention is to provide a multipolymer fluid loss reducer for oil well cement and a preparation method thereof, so as to solve the technical problems of poor fluid loss reducing performance and poor temperature and salt resistance of the fluid loss reducer in the prior art.

[0005] In order to achieve the above object, the present invention adopts the following technical solutions:

[0006] The invention provides a multi-polymer fluid loss reducer for oil well cement. The multi-polymer fluid loss reducer is composed of the following components in parts by weight: 42-56 parts of high molecular weight polymer, 4-6 parts of bentonite, 1-3 parts of disodium ethylenediaminetetraacetate, 10-13 parts of composite hydrating agent, 8-12 parts of distilled water and 0.2-0.4 parts of ammonium persulfate, wherein the high molecular weight polymer is prepared from dimethylaminopropyl acrylamide, 2-acrylamide-2-methylpropane sulfonic acid, glycidyl methacrylate, sodium 3-prop-2-enoyloxypropane-1-sulfonate and 2-aminoethanethiol, and the composite hydrating agent is prepared from sodium hydroxide, acrylic acid, 2-acrylamide-2-methylpropane sulfonic acid, sodium lignin sulfonate, citric acid, urea, choline chloride, corn fiber and butyl succinic anhydride.

[0007] Preferably, the method for preparing the high molecular weight polymer comprises the following steps:

[0008] Q1: Add dimethylaminopropyl acrylamide, 2-acrylamido-2-methylpropanesulfonic acid and glycidyl methacrylate to a container containing dimethyl sulfoxide, stir and dissolve, then introduce nitrogen, then add azobisisobutyronitrile, heat and react, after the reaction is completed, cool, precipitate, filter, dissolve, dialyze, concentrate and freeze-dry to obtain polymer 1;

[0009] Q2: Add dimethylaminopropyl acrylamide, sodium 3-prop-2-enoyloxypropane-1-sulfonate and 2-aminoethanethiol into distilled water, stir and dissolve, then introduce nitrogen, then add azobisisobutyronitrile, heat and react, after the reaction is completed, adjust the pH, precipitate, filter, dissolve, dialyze, concentrate, freeze-dry and grind to obtain polymer 2;

[0010] Q3: Add polymer 1 and polymer 2 to distilled water, stir for reaction, dialyze, rotary evaporate, freeze-dry and grind to obtain a high molecular weight polymer.

[0011] In the above process, the synthetic reaction formula of the polymer is as follows:

[0012]

[0013] Preferably, in Q1, the dosage ratio of dimethylaminopropyl acrylamide, 2-acrylamido-2-methylpropanesulfonic acid, glycidyl methacrylate, dimethyl sulfoxide and azobisisobutyronitrile is (5.78-6.8) g: (3.18-3.22) g: (1.03-1.3) g: (45-55) mL: (0.023-0.025) g, the nitrogen is introduced for 30-45 min, the temperature of the reaction is 60-70° C., the time is 10-12 h, the reaction is added to anhydrous ethanol for precipitation, added to distilled water for dissolution, and dialyzed for 7-9 d using a dialysis bag with a molecular weight cutoff of 10,000 Da.

[0014] Preferably, in Q2, the dosage ratio of dimethylaminopropyl acrylamide, 3-prop-2-enoyloxypropane-1-sulfonic acid sodium, 2-aminoethanethiol, distilled water and azobisisobutyronitrile is (5.79-6.12) g: (4.24-4.45) g: (0.1-0.15) g: (50-60) mL: (0.1-0.15) g, the nitrogen is introduced for 30-45 min, the temperature is raised to 50-60° C., the reaction time is 10-12 h, the pH is adjusted to 7-7.2 with 1 mol / L sodium hydroxide solution, the mixture is added to anhydrous ethanol for precipitation, added to distilled water for dissolution, and dialyzed for 7-9 d with a dialysis bag with a molecular weight cutoff of 10,000 Da.

[0015] Preferably, in Q3, the usage ratio of polymer 1, polymer 2 and distilled water is (0.27-0.54) g: (1.39-2.78) g: (15-20) mL, the stirring reaction time is 20-24 h, and the dialysis is performed for 5-7 d using a dialysis bag with a molecular weight cutoff of 30,000 Da.

[0016] Preferably, the preparation method of the composite hydrating agent comprises the following steps:

[0017] S1: adding sodium hydroxide to a container containing distilled water, stirring to dissolve, dropping acrylic acid into the sodium hydroxide solution in an ice water bath, then adding 2-acrylamido-2-methylpropanesulfonic acid, sodium lignin sulfonate and citric acid respectively, adjusting the pH, stirring until completely dissolved, adding ammonium persulfate and N,N'-methylenebisacrylamide, heating in an oil bath with stirring to react, soaking, washing, soaking, freezing, and drying after the reaction is completed to obtain a gel;

[0018] S2: urea and choline chloride are mixed and heated to obtain a transparent liquid, and then corn fiber is added to the transparent liquid, butyl succinic anhydride is added under stirring, and heated to react. After the reaction is completed, precipitation is performed, centrifugation and washing, dialyzing, and freeze-drying are performed to obtain modified fiber;

[0019] S3: adding the gel into distilled water, stirring with ultrasound, then adding the modified fiber, freezing after stirring, vacuum drying, and crushing to obtain a composite hydrating agent.

[0020] In the above process, sodium lignin sulfonate is used as a bio-based skeleton, acrylic acid and 2-acrylamido-2-methylpropanesulfonic acid are used as raw materials, citric acid is used as a modifier, ammonium persulfate is used as an initiator, and N,N'-methylenebisacrylamide is used as a cross-linking agent. The gel is prepared by aqueous solution polymerization, and then a mixed solution of urea and choline chloride is used as a homogeneous reaction medium, butyl succinic anhydride is selected to modify the corn fiber to obtain modified fiber, and then the gel and the modified fiber are mixed to obtain a composite hydrating agent.

[0021] Preferably, in S1, the amount ratio of sodium hydroxide, distilled water, acrylic acid, 2-acrylamido-2-methylpropane sulfonic acid, sodium lignin sulfonate, citric acid, ammonium persulfate and N,N'-methylenebisacrylamide is (3-6) g: (20-40) mL: (9-18) g: (3-5) g: (1.2-2) g: (1-1.5) g: (0.14-0.2) g: (0.016-0.03) g, the pH is adjusted to 6-7, the oil bath heating temperature is 50-60°C, the reaction time is 10-15 min, first soak in anhydrous ethanol for 5-10 min, then wash with distilled water 3-5 times, and then soak in distilled water for 5-8 min, the freezing time is 5-7 h, the drying temperature is 80-85°C, and the time is 8-10 h.

[0022] Preferably, in S2, the mass ratio of urea, choline chloride, corn fiber and butyl succinic anhydride is (2-2.5): (2.1-2.8): (2-2.67): (2.18-2.96), the blending heating temperature is 70-80°C, the time is 2-4h, the heating reaction temperature is 60-70°C, the time is 10-15min, precipitation is carried out with anhydrous ethanol, and dialyzed in distilled water with a dialysis membrane with a molecular weight cutoff of 1000Da for 70-84h; in S3, the amount ratio of gel, distilled water and modified fiber is (8-12)g: (10-15)mL: (2-4)g, the ultrasonic stirring time is 10-15min, and the stirring time is 30-45min.

[0023] Preferably, the method for preparing the multi-polymer fluid loss reducer for oil well cement comprises the following steps:

[0024] Step 1: mixing a high molecular polymer, bentonite, disodium ethylenediaminetetraacetate and a composite hydrating agent to obtain a mixed material;

[0025] Step 2: Add distilled water to the mixture, stir, add ammonium persulfate, heat and stir to react, and after the reaction is completed, cool, filter and dry to obtain a multi-polymer oil well cement fluid loss reducer.

[0026] Preferably, in the step 1, the mixing time is 2-4 hours; in the step 2, the stirring time is 30-45 minutes, the heating and stirring temperature is 60-80° C., and the reaction time is 20-30 minutes.

[0027] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are:

[0028] 1. The present invention first uses dimethylaminopropyl acrylamide, 2-acrylamido-2-methylpropane sulfonic acid, glycidyl methacrylate, 3-prop-2-enoyloxypropane-1-sodium sulfonate and 2-aminoethanethiol as raw materials to prepare a high molecular polymer, and then uses sodium hydroxide, acrylic acid, 2-acrylamido-2-methylpropane sulfonic acid, sodium lignin sulfonate, citric acid, urea, choline chloride, corn fiber and butyl succinic anhydride as raw materials to prepare a composite hydrating agent. In the process of preparing the fluid loss reducer, the high molecular polymer and the composite hydrating agent are added, which can effectively improve the fluid loss reducing property, temperature resistance and salt resistance of the fluid loss reducer, and can also improve the fluidity of the fluid loss reducer to cement slurry.

[0029] 2. The present invention uses dimethylaminopropyl acrylamide, 2-acrylamido-2-methylpropanesulfonic acid, glycidyl methacrylate, 3-prop-2-enoyloxypropane-1-sulfonic acid sodium and 2-aminoethanethiol as raw materials to prepare a high molecular polymer, and uses the high molecular polymer as one of the main raw materials of a fluid loss reducer, so that the high molecular polymer has high efficiency in fluid loss reduction performance, good temperature resistance and salt resistance, and enhances the strength of cement slurry. The hydrophilic groups such as amide groups and sulfonic acid groups contained in the high molecular polymer can form hydrogen bonds with water molecules, thereby enhancing the water adsorption capacity of the polymer, and the cross-linked structure contained in the high molecular polymer further improves the water retention of the polymer. Performance: When high molecular polymer is added to cement slurry as a fluid loss reducer, the hydrophilic group can be adsorbed on the surface of cement particles to form a protective film to prevent water loss between cement particles. The presence of polymer chain segments can also slow down the diffusion rate of water in cement slurry and improve the water loss reduction effect. High molecular polymer has high thermal stability and can maintain stable structure and performance at high temperatures. The negatively charged groups such as sulfonic acid groups it contains form a charge shielding effect to enhance stability in high salinity environments. At the same time, during the cement hydration process, the high molecular polymer reacts with hydration products such as calcium hydroxide to form chemical bonds, enhance the interaction force, and improve the strength of the cement slurry.

[0030] 3. The present invention uses sodium hydroxide, acrylic acid, 2-acrylamido-2-methylpropane sulfonic acid, sodium lignin sulfonate, citric acid, urea, choline chloride, corn fiber and butyl succinic anhydride as raw materials to prepare a composite hydrating agent. The hydrophilic groups contained in the composite hydrating agent form hydrogen bonds with water molecules, which significantly enhances the water adsorption capacity of the composite hydrating agent, effectively prevents water loss between cement particles, and improves the water loss reduction effect. The sulfonic acid groups contained in the composite hydrating agent can also improve its heat resistance and salt resistance. At the same time, the gel component can form a protective film on the surface of cement particles to prevent water evaporation, and the presence of the modified fiber fills the micropores and cracks in the cement stone, thereby improving the mechanical properties of the cement stone. DETAILED DESCRIPTION

[0031] The following will be described clearly and completely in conjunction with the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0032] Example 1: This example discloses a method for preparing a high molecular weight polymer, comprising the following steps:

[0033] Q1: 6.14 g of dimethylaminopropyl acrylamide, 3.2 g of 2-acrylamido-2-methylpropanesulfonic acid and 1.16 g of glycidyl methacrylate were added to a container containing 50 mL of dimethyl sulfoxide, stirred and dissolved, and nitrogen was introduced for 30 min, and then 0.024 g of azobisisobutyronitrile was added, and the temperature was raised to 70°C for reaction for 12 h. After the reaction was completed, the mixture was cooled, added to anhydrous ethanol for precipitation, filtered, added to distilled water for dissolution, dialyzed using a dialysis bag with a molecular weight cutoff of 10,000 Da for 7 days, concentrated, and freeze-dried to obtain polymer 1;

[0034] Q2: 6.01 g of dimethylaminopropyl acrylamide, 4.4 g of sodium 3-prop-2-enoyloxypropane-1-sulfonate and 0.125 g of 2-aminoethanethiol were added to 55 mL of distilled water, stirred and dissolved, and nitrogen was introduced for 45 min, followed by adding 0.12 g of azobisisobutyronitrile, and the temperature was raised to 60°C for reaction for 12 h. After the reaction, the pH was adjusted to 7 with 1 mol / L sodium hydroxide solution, and the mixture was added to anhydrous ethanol for precipitation, filtered, added to distilled water for dissolution, dialyzed with a dialysis bag with a molecular weight cutoff of 10,000 Da for 7 d, concentrated, freeze-dried, and ground to obtain polymer 2;

[0035] Q3: 0.4 g of polymer 1 and 1.98 g of polymer 2 were added to 17.5 mL of distilled water, stirred for reaction for 24 h, and then dialyzed for 7 days using a dialysis bag with a molecular weight cutoff of 30,000 Da. The mixture was rotary evaporated, freeze-dried, and ground to obtain a high molecular weight polymer.

[0036] This embodiment discloses a method for preparing a composite hydrating agent, comprising the following steps:

[0037] S1: Add 4.5g of sodium hydroxide to a container containing 30mL of distilled water, stir to dissolve, add 13.5g of acrylic acid dropwise to the sodium hydroxide solution in an ice-water bath, then add 4g of 2-acrylamido-2-methylpropanesulfonic acid, 1.6g of sodium lignin sulfonate and 1.25g of citric acid respectively, adjust the pH to 6, stir until completely dissolved, add 0.17g of ammonium persulfate and 0.023g of N,N'-methylenebisacrylamide, heat and stir in an oil bath at 55°C for 15min, after the reaction is completed, first soak in anhydrous ethanol for 10min, then wash with distilled water 3 times, then soak in distilled water for 5min, freeze for 5h, and dry at 85°C for 8h to obtain a gel;

[0038] S2: 2.25 g urea and 2.45 g choline chloride were mixed and heated at 80°C for 2 h to obtain a transparent liquid, and then 2.33 g corn fiber was added to the transparent liquid, 2.57 g butyl succinic anhydride was added under stirring, and the mixture was heated at 70°C for 15 min. After the reaction, the mixture was precipitated with anhydrous ethanol, centrifuged and washed, and dialyzed in distilled water for 84 h using a dialysis membrane with a molecular weight cutoff of 1000 Da, and freeze-dried to obtain modified fiber;

[0039] S3: 10 g of gel was added to 12.5 mL of distilled water, and ultrasonically stirred for 15 min. Then 3 g of modified fiber was added, and the mixture was stirred for 45 min, frozen, vacuum dried, and crushed to obtain a composite hydrating agent.

[0040] The present embodiment discloses a multi-polymer fluid loss reducer for oil well cement, which is composed of the following components in parts by weight: 49 parts of high molecular polymer, 5 parts of bentonite, 2 parts of disodium ethylenediaminetetraacetate, 11.5 parts of composite hydrating agent, 10 parts of distilled water, and 0.3 parts of ammonium persulfate.

[0041] This embodiment discloses a method for preparing a multi-polymer fluid loss reducer for oil well cement, comprising the following steps:

[0042] Step 1: Mixing the high molecular polymer, bentonite, disodium ethylenediaminetetraacetate and a composite hydrating agent for 4 hours to obtain a mixed material;

[0043] Step 2: Add distilled water to the mixture, stir for 45 minutes, add ammonium persulfate, heat and stir at 80°C for 30 minutes, and after the reaction is completed, cool, filter and dry to obtain a multipolymer fluid loss reducer for oil well cement.

[0044] Example 2: This example discloses a method for preparing a high molecular weight polymer, comprising the following steps:

[0045] Q1: 5.78 g of dimethylaminopropyl acrylamide, 3.18 g of 2-acrylamido-2-methylpropanesulfonic acid and 1.03 g of glycidyl methacrylate were added to a container containing 45 mL of dimethyl sulfoxide, stirred and dissolved, and nitrogen was introduced for 30 min, then 0.023 g of azobisisobutyronitrile was added, and the temperature was raised to 70°C for reaction for 12 h. After the reaction was completed, the mixture was cooled, added to anhydrous ethanol for precipitation, filtered, added to distilled water for dissolution, dialyzed for 7 days using a dialysis bag with a molecular weight cutoff of 10,000 Da, concentrated, and freeze-dried to obtain polymer 1;

[0046] Q2: 5.79 g of dimethylaminopropyl acrylamide, 4.24 g of sodium 3-prop-2-enoyloxypropane-1-sulfonate and 0.1 g of 2-aminoethanethiol were added to 50 mL of distilled water, stirred and dissolved, and nitrogen was introduced for 45 min, followed by adding 0.1 g of azobisisobutyronitrile, and the temperature was raised to 60°C for reaction for 12 h. After the reaction, the pH was adjusted to 7 with 1 mol / L sodium hydroxide solution, and the mixture was added to anhydrous ethanol for precipitation, filtered, added to distilled water for dissolution, dialyzed with a dialysis bag with a molecular weight cutoff of 10,000 Da for 7 d, concentrated, freeze-dried, and ground to obtain polymer 2;

[0047] Q3: 0.27 g of polymer 1 and 1.39 g of polymer 2 were added to 15 mL of distilled water, stirred for reaction for 24 h, and then dialyzed for 7 days using a dialysis bag with a molecular weight cutoff of 30,000 Da. The mixture was rotary evaporated, freeze-dried, and ground to obtain a high molecular weight polymer.

[0048] This embodiment discloses a method for preparing a composite hydrating agent, comprising the following steps:

[0049] S1: Add 3g of sodium hydroxide to a container containing 20mL of distilled water, stir to dissolve, add 9g of acrylic acid dropwise to the sodium hydroxide solution in an ice-water bath, then add 3g of 2-acrylamido-2-methylpropanesulfonic acid, 1.2g of sodium lignin sulfonate and 1.5g of citric acid respectively, adjust the pH to 6, stir until completely dissolved, add 0.14g of ammonium persulfate and 0.016g of N,N'-methylenebisacrylamide, heat and stir in an oil bath at 55°C for 15min, after the reaction, first soak in anhydrous ethanol for 10min, then wash with distilled water 3 times, then soak in distilled water for 5min, freeze for 5h, and dry at 85°C for 8h to obtain a gel;

[0050] S2: 2.5 g urea and 2.1 g choline chloride were mixed and heated at 80°C for 2 h to obtain a transparent liquid, and then 2 g corn fiber was added to the transparent liquid, 2.18 g butyl succinic anhydride was added under stirring, and the mixture was heated at 70°C for 15 min. After the reaction, the mixture was precipitated with anhydrous ethanol, centrifuged and washed, and dialyzed in distilled water for 84 h using a dialysis membrane with a molecular weight cutoff of 1000 Da, and freeze-dried to obtain modified fiber;

[0051] S3: 8 g of gel was added to 10 mL of distilled water, and ultrasonically stirred for 15 min. Then, 2 g of modified fiber was added, and the mixture was stirred for 45 min, frozen, vacuum dried, and crushed to obtain a composite hydrating agent.

[0052] The present embodiment discloses a multi-polymer fluid loss reducer for oil well cement, which is composed of the following components in parts by weight: 42 parts of high molecular polymer, 4 parts of bentonite, 1 part of disodium ethylenediaminetetraacetate, 10 parts of composite hydrating agent, 8 parts of distilled water, and 0.2 parts of ammonium persulfate.

[0053] This embodiment discloses a method for preparing a multi-polymer fluid loss reducer for oil well cement, comprising the following steps:

[0054] Step 1: Mixing the high molecular polymer, bentonite, disodium ethylenediaminetetraacetate and a composite hydrating agent for 4 hours to obtain a mixed material;

[0055] Step 2: Add distilled water to the mixture, stir for 45 minutes, add ammonium persulfate, heat and stir at 80°C for 30 minutes, and after the reaction is completed, cool, filter and dry to obtain a multipolymer fluid loss reducer for oil well cement.

[0056] Example 3: This example discloses a method for preparing a high molecular weight polymer, comprising the following steps:

[0057] Q1: 6.8 g of dimethylaminopropyl acrylamide, 3.22 g of 2-acrylamido-2-methylpropanesulfonic acid and 1.3 g of glycidyl methacrylate were added to a container containing 55 mL of dimethyl sulfoxide, stirred and dissolved, and nitrogen was introduced for 30 min, and then 0.025 g of azobisisobutyronitrile was added, and the temperature was raised to 70°C for reaction for 12 h. After the reaction was completed, the mixture was cooled, added to anhydrous ethanol for precipitation, filtered, added to distilled water for dissolution, dialyzed using a dialysis bag with a molecular weight cutoff of 10,000 Da for 7 days, concentrated, and freeze-dried to obtain polymer 1;

[0058] Q2: 6.12 g of dimethylaminopropyl acrylamide, 4.45 g of sodium 3-prop-2-enoyloxypropane-1-sulfonate and 0.15 g of 2-aminoethanethiol were added to 60 mL of distilled water, stirred and dissolved, and nitrogen was introduced for 45 min, followed by adding 0.15 g of azobisisobutyronitrile, and the temperature was raised to 60°C for reaction for 12 h. After the reaction, the pH was adjusted to 7 with 1 mol / L sodium hydroxide solution, and the mixture was added to anhydrous ethanol for precipitation, filtered, added to distilled water for dissolution, dialyzed with a dialysis bag with a molecular weight cutoff of 10,000 Da for 7 days, concentrated, freeze-dried, and ground to obtain polymer 2;

[0059] Q3: 0.54 g of polymer 1 and 2.78 g of polymer 2 were added to 20 mL of distilled water, stirred for reaction for 24 h, and then dialyzed for 7 days using a dialysis bag with a molecular weight cutoff of 30,000 Da. The mixture was rotary evaporated, freeze-dried, and ground to obtain a high molecular weight polymer.

[0060] This embodiment discloses a method for preparing a composite hydrating agent, comprising the following steps:

[0061] S1: Add 6 g of sodium hydroxide to a container containing 40 mL of distilled water, stir to dissolve, add 18 g of acrylic acid dropwise to the sodium hydroxide solution in an ice-water bath, then add 5 g of 2-acrylamido-2-methylpropanesulfonic acid, 2 g of sodium lignin sulfonate and 1 g of citric acid respectively, adjust the pH to 6, stir until completely dissolved, add 0.2 g of ammonium persulfate and 0.03 g of N,N'-methylenebisacrylamide, heat and stir in an oil bath at 55°C for 15 min, after the reaction is completed, first soak in anhydrous ethanol for 10 min, then wash with distilled water 3 times, then soak in distilled water for 5 min, freeze for 5 h, and dry at 85°C for 8 h to obtain a gel;

[0062] S2: 2 g urea and 2.8 g choline chloride were mixed and heated at 80°C for 2 h to obtain a transparent liquid, and then 2.67 g corn fiber was added to the transparent liquid, 2.96 g butyl succinic anhydride was added under stirring, and the mixture was heated at 70°C for 15 min. After the reaction, the mixture was precipitated with anhydrous ethanol, centrifuged and washed, and dialyzed in distilled water for 84 h using a dialysis membrane with a molecular weight cutoff of 1000 Da, and freeze-dried to obtain modified fiber;

[0063] S3: 12 g of gel was added to 15 mL of distilled water, and ultrasonically stirred for 15 min. Then 4 g of modified fiber was added, stirred for 45 min, and then frozen, vacuum dried, and crushed to obtain a composite hydrating agent.

[0064] The present embodiment discloses a multi-polymer fluid loss reducer for oil well cement, which is composed of the following components in parts by weight: 56 parts of high molecular polymer, 6 parts of bentonite, 3 parts of disodium ethylenediaminetetraacetate, 13 parts of composite hydrating agent, 12 parts of distilled water, and 0.4 parts of ammonium persulfate.

[0065] This embodiment discloses a method for preparing a multi-polymer fluid loss reducer for oil well cement, comprising the following steps:

[0066] Step 1: Mixing the high molecular polymer, bentonite, disodium ethylenediaminetetraacetate and a composite hydrating agent for 4 hours to obtain a mixed material;

[0067] Step 2: Add distilled water to the mixture, stir for 45 minutes, add ammonium persulfate, heat and stir at 80°C for 30 minutes, and after the reaction is completed, cool, filter and dry to obtain a multipolymer fluid loss reducer for oil well cement.

[0068] Example 4: This example discloses a method for preparing a high molecular weight polymer, comprising the following steps:

[0069] Q1: 6.47 g of dimethylaminopropyl acrylamide, 3.19 g of 2-acrylamido-2-methylpropanesulfonic acid and 1.09 g of glycidyl methacrylate were added to a container containing 48 mL of dimethyl sulfoxide, stirred and dissolved, and nitrogen was introduced for 30 min, and then 0.024 g of azobisisobutyronitrile was added, and the temperature was raised to 70°C for reaction for 12 h. After the reaction was completed, the mixture was cooled, added to anhydrous ethanol for precipitation, filtered, added to distilled water for dissolution, dialyzed using a dialysis bag with a molecular weight cutoff of 10,000 Da for 7 days, concentrated, and freeze-dried to obtain polymer 1;

[0070] Q2: 5.83 g of dimethylaminopropyl acrylamide, 4.28 g of sodium 3-prop-2-enoyloxypropane-1-sulfonate and 0.13 g of 2-aminoethanethiol were added to 52 mL of distilled water, stirred and dissolved, and nitrogen was introduced for 45 min, followed by adding 0.11 g of azobisisobutyronitrile, and the temperature was raised to 60°C for reaction for 12 h. After the reaction, the pH was adjusted to 7 with 1 mol / L sodium hydroxide solution, and the mixture was added to anhydrous ethanol for precipitation, filtered, added to distilled water for dissolution, dialyzed with a dialysis bag with a molecular weight cutoff of 10,000 Da for 7 d, concentrated, freeze-dried, and ground to obtain polymer 2;

[0071] Q3: 0.31 g of polymer 1 and 1.57 g of polymer 2 were added to 16 mL of distilled water, stirred for reaction for 24 h, and then dialyzed for 7 days using a dialysis bag with a molecular weight cutoff of 30,000 Da. The mixture was rotary evaporated, freeze-dried, and ground to obtain a high molecular weight polymer.

[0072] This embodiment discloses a method for preparing a composite hydrating agent, comprising the following steps:

[0073] S1: Add 4g of sodium hydroxide to a container containing 25mL of distilled water, stir to dissolve, add 11g of acrylic acid dropwise to the sodium hydroxide solution in an ice-water bath, then add 3.5g of 2-acrylamido-2-methylpropanesulfonic acid, 1.4g of sodium lignin sulfonate and 1.1g of citric acid respectively, adjust the pH to 6, stir until completely dissolved, add 0.15g of ammonium persulfate and 0.021g of N,N'-methylenebisacrylamide, heat and stir in an oil bath at 55°C for 15min, after the reaction, first soak in anhydrous ethanol for 10min, then wash with distilled water 3 times, then soak in distilled water for 5min, freeze for 5h, and dry at 85°C for 8h to obtain a gel;

[0074] S2: 2.1 g urea and 2.3 g choline chloride were mixed and heated at 80°C for 2 h to obtain a transparent liquid, and then 2.11 g corn fiber was added to the transparent liquid, 2.25 g butyl succinic anhydride was added under stirring, and the mixture was heated at 70°C for 15 min. After the reaction, the mixture was precipitated with anhydrous ethanol, centrifuged and washed, and dialyzed in distilled water for 84 h using a dialysis membrane with a molecular weight cutoff of 1000 Da, and freeze-dried to obtain modified fiber;

[0075] S3: 9 g of gel was added to 11 mL of distilled water, and ultrasonically stirred for 15 min. Then, 2.5 g of modified fiber was added, and the mixture was stirred for 45 min, frozen, vacuum dried, and crushed to obtain a composite hydrating agent.

[0076] The present embodiment discloses a multi-polymer fluid loss reducer for oil well cement, which is composed of the following components in parts by weight: 44 parts of high molecular polymer, 4.5 parts of bentonite, 1.5 parts of disodium ethylenediaminetetraacetate, 11 parts of composite hydrating agent, 9 parts of distilled water, and 0.25 parts of ammonium persulfate.

[0077] This embodiment discloses a method for preparing a multi-polymer fluid loss reducer for oil well cement, comprising the following steps:

[0078] Step 1: Mixing the high molecular polymer, bentonite, disodium ethylenediaminetetraacetate and a composite hydrating agent for 4 hours to obtain a mixed material;

[0079] Step 2: Add distilled water to the mixture, stir for 45 minutes, add ammonium persulfate, heat and stir at 80°C for 30 minutes, and after the reaction is completed, cool, filter and dry to obtain a multipolymer fluid loss reducer for oil well cement.

[0080] Comparative Example 1: Compared with Example 1, in the process of preparing the high molecular weight polymer in Comparative Example 1, 2-aminoethanethiol was not added, and other conditions remained unchanged.

[0081] Comparative Example 2: Compared with Example 1, in the process of preparing the composite hydrating agent in Comparative Example 2, no 2-acrylamide-2-methylpropanesulfonic acid is added, and other conditions remain unchanged.

[0082] Comparative Example 3: Compared with Example 1, in Comparative Example 3, during the preparation of the multi-polymer fluid loss reducer for oil well cement, no high molecular weight polymer is added, and other conditions remain unchanged.

[0083] Comparative Example 4: Compared with Example 1, in Comparative Example 4, during the preparation of the multi-polymer fluid loss reducer for oil well cement, no composite hydrating agent was added, and other conditions remained unchanged.

[0084] Experimental example: fluid loss reduction performance test, the obtained samples were added to the same cement slurry according to different mass fractions, and the fluid loss performance was tested at 200°C. The test results are shown in Table 1:

[0085] Table 1

[0086]

[0087] It can be seen from the test results in Table 1 that as the mass fraction of the sample increases, the water loss of the cement slurry gradually decreases, and the water loss of the samples of Examples 1-4 to the cement slurry is at a relatively low level, indicating that the fluid loss reducer prepared by the method of Examples 1-4 has excellent fluid loss reduction performance. By comparing Comparative Example 1 with Examples 1-4, it can be seen that the addition of 2-aminoethanethiol can effectively improve the fluid loss reduction performance of the fluid loss reducer; by comparing Comparative Example 2 with Examples 1-4, it can be seen that the addition of 2-acrylamido-2-methylpropanesulfonic acid can effectively improve the fluid loss reduction performance of the fluid loss reducer; by comparing Comparative Example 3 with Examples 1-4, it can be seen that the addition of a high molecular polymer can effectively improve the fluid loss reduction performance of the fluid loss reducer; by comparing Comparative Example 4 with Examples 1-4, it can be seen that the addition of a composite hydrating agent can effectively improve the fluid loss reduction performance of the fluid loss reducer.

[0088] Temperature resistance test: the obtained samples were added into the same cement slurry at an addition amount of 2wt%, and the water loss was tested at different temperatures. The test results are shown in Table 2:

[0089] Table 2

[0090]

[0091] It can be seen from the test results in Table 2 that as the temperature increases, the water loss of the samples of Examples 1-4 to the cement slurry is at a gentle level, indicating that the fluid loss reducer prepared by the method of Examples 1-4 has excellent temperature resistance. By comparing Comparative Example 1 with Examples 1-4, it can be seen that the addition of 2-aminoethanethiol can effectively improve the temperature resistance of the fluid loss reducer; by comparing Comparative Example 2 with Examples 1-4, it can be seen that the addition of 2-acrylamide-2-methylpropanesulfonic acid can effectively improve the temperature resistance of the fluid loss reducer; by comparing Comparative Example 3 with Examples 1-4, it can be seen that the addition of a high molecular polymer can effectively improve the temperature resistance of the fluid loss reducer; by comparing Comparative Example 4 with Examples 1-4, it can be seen that the addition of a composite hydrating agent can effectively improve the temperature resistance of the fluid loss reducer.

[0092] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

[0093] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to only specific implementation methods. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. A multi-polymer oil well cement fluid loss reducer, characterized in that: The invention is composed of the following components in parts by weight: 42-56 parts of a high molecular polymer, 4-6 parts of bentonite, 1-3 parts of disodium ethylenediaminetetraacetate, 10-13 parts of a composite hydrating agent, 8-12 parts of distilled water, and 0.2-0.4 parts of ammonium persulfate, wherein the high molecular polymer is prepared from dimethylaminopropyl acrylamide, 2-acrylamide-2-methylpropane sulfonic acid, glycidyl methacrylate, sodium 3-prop-2-enoyloxypropane-1-sulfonate and 2-aminoethanethiol, and the composite hydrating agent is prepared from sodium hydroxide, acrylic acid, 2-acrylamide-2-methylpropane sulfonic acid, sodium lignin sulfonate, citric acid, urea, choline chloride, corn fiber and butyl succinic anhydride; The method for preparing the high molecular polymer comprises the following steps: Q1: Add dimethylaminopropyl acrylamide, 2-acrylamido-2-methylpropanesulfonic acid and glycidyl methacrylate to a container containing dimethyl sulfoxide, stir and dissolve, then introduce nitrogen, then add azobisisobutyronitrile, heat and react, after the reaction is completed, cool, precipitate, filter, dissolve, dialyze, concentrate, and freeze-dry to obtain polymer 1; in Q1, dimethylaminopropyl acrylamide, 2-acrylamido-2-methylpropanesulfonic acid, glycidyl methacrylate, dimethylsulfoxide The dosage ratio of sulfone and azobisisobutyronitrile is (5.78-6.8) g: (3.18-3.22) g: (1.03-1.3) g: (45-55) mL: (0.023-0.025) g, the nitrogen is introduced for 30-45 min, the temperature is raised to 60-70°C, the reaction time is 10-12 h, the product is added to anhydrous ethanol for precipitation, added to distilled water for dissolution, and dialyzed for 7-9 days using a dialysis bag with a molecular weight cutoff of 10000 Da; Q2: Add dimethylaminopropyl acrylamide, sodium 3-prop-2-enoyloxypropane-1-sulfonate and 2-aminoethanethiol to distilled water, stir and dissolve, then introduce nitrogen, then add azobisisobutyronitrile, heat and react, after the reaction is completed, adjust the pH, precipitate, filter, dissolve, dialyze, concentrate, freeze-dry, grind, and obtain polymer 2; in Q2, the amount ratio of dimethylaminopropyl acrylamide, sodium 3-prop-2-enoyloxypropane-1-sulfonate, 2-aminoethanethiol, distilled water and azobisisobutyronitrile is: (5.79-6.12) g: (4.24-4.45) g: (0.1-0.15) g: (50-60) mL: (0.1-0.15) g, nitrogen gas introduction time is 30-45 min, temperature reaction temperature is 50-60 ° C, time is 10-12 h, pH = 7-7.2 is adjusted with 1 mol / L sodium hydroxide solution, added to anhydrous ethanol for precipitation, added to distilled water for dissolution, dialyzed with a dialysis bag with a molecular weight cutoff of 10000 Da for 7-9 days; Q3: Add polymer 1 and polymer 2 to distilled water, stir for reaction, dialyze, rotary evaporate, freeze-dry, grind, and obtain a high molecular weight polymer; in Q3, the amount ratio of polymer 1, polymer 2 and distilled water is (0.27-0.54) g: (1.39-2.78) g: (15-20) mL, the stirring reaction time is 20-24 h, and the dialysis bag with a molecular weight cutoff of 30000 Da is used for dialysis for 5-7 days; The preparation method of the composite hydrating agent comprises the following steps: S1: adding sodium hydroxide to a container containing distilled water, stirring to dissolve, dropping acrylic acid into the sodium hydroxide solution in an ice-water bath, then adding 2-acrylamido-2-methylpropanesulfonic acid, sodium lignin sulfonate and citric acid respectively, adjusting the pH, stirring until completely dissolved, adding ammonium persulfate and N,N'-methylenebisacrylamide, heating in an oil bath and stirring to react, soaking, washing, soaking, freezing, and drying to obtain a gel; in S1, sodium hydroxide, distilled water, acrylic acid, 2-acrylamido-2-methylpropanesulfonic acid, sodium lignin sulfonate, citric acid, ammonium persulfate and N,N'-methylenebisacrylamide are added, and the reaction is stirred and reacted. After the reaction is completed, soaking, washing, soaking, freezing, and drying are performed to obtain a gel; The dosage ratio of N'-methylenebisacrylamide is (3-6) g: (20-40) mL: (9-18) g: (3-5) g: (1.2-2) g: (1-1.5) g: (0.14-0.2) g: (0.016-0.03) g, adjust pH=6-7, oil bath heating temperature is 50-60℃, reaction time is 10-15min, first soak in anhydrous ethanol for 5-10min, then wash with distilled water for 3-5 times, then soak in distilled water for 5-8min, freeze for 5-7h, dry at 80-85℃ for 8-10h; S2: urea and choline chloride are mixed and heated to obtain a transparent liquid, corn fiber is added to the transparent liquid, butyl succinic anhydride is added under stirring, and the mixture is heated for reaction. After the reaction is completed, the mixture is precipitated, centrifuged, washed, dialyzed, and freeze-dried to obtain modified fiber. In S2, the mass ratio of urea, choline chloride, corn fiber, and butyl succinic anhydride is (2-2.5): (2.1-2.8): (2-2.67): (2.18-2.96). The heating temperature is 70-80°C for 2-4 hours, the heating reaction temperature is 60-70°C for 10-15 minutes, anhydrous ethanol is used for precipitation, and a dialysis membrane with a molecular weight cutoff of 1000Da is used for 70-84 hours in distilled water; in S3, the amount ratio of gel, distilled water and modified fiber is (8-12) g: (10-15) mL: (2-4) g, the ultrasonic stirring time is 10-15 minutes, and the stirring time is 30-45 minutes; S3: adding the gel into distilled water, stirring with ultrasound, then adding the modified fiber, freezing after stirring, vacuum drying, and crushing to obtain a composite hydrating agent.

2. The method for preparing the multi-polymer fluid loss reducer for oil well cement according to claim 1, characterized in that: The following steps are involved: Step 1: mixing a high molecular polymer, bentonite, disodium ethylenediaminetetraacetate and a composite hydrating agent to obtain a mixed material; Step 2: Add distilled water to the mixture, stir, add ammonium persulfate, heat and stir to react, and after the reaction is completed, cool, filter and dry to obtain a multi-polymer oil well cement fluid loss reducer.

3. The method for preparing the multi-polymer fluid loss reducer for oil well cement according to claim 2, characterized in that: In the step 1, the mixing time is 2-4 hours; in the step 2, the stirring time is 30-45 minutes, the heating and stirring temperature is 60-80° C., and the reaction time is 20-30 minutes.

Citation Information

Patent Citations

  • Monomer composition containing unsaturated polyalkylene glycol ether-based monomer, method for producing composition, polymer obtained using composition, and method for producing polymer

    CN103119074A

  • Oil well cement fluid loss agent for solving problem of thickening and core wrapping of cement paste and preparation method thereof

    CN111153624A